Scientific Output on Bovine Viral Diarrhoea: A Scientometric Study - Singh, Nirmal; Chavan, Shankar B.; Malhotra, Puneet (Journal of Information and Knowledge, 2018)
The study analyses the dynamics of scientific output on ‘Bovine Viral Diarrhoea’ (BVD) published in journals, applying scientometric tools. The data was gathered from ‘Scopus’ database, conducting an advanced search for phrase ‘Bovine Viral Diarrhoea’ and substitute terms including ‘Bovine Virus Diarrhoea’, ‘Bovine Viral Diarrhea’ and ‘Bovine Virus Diarrhea’ as main operators for analytical purposes. The retrieved data was filtered for English language journal articles, for the period up to 31st December 2015, yielding 3561 relevant results. The different scientometric indicators of literature on BVD including it is growth, authorship, collaboration, publication pattern, geographical distribution, etc. were computed. International collaboration and keyword landscapes were visualized.